(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Laboratory studies were carried out to evaluate whether irradiation of pupae resulting from larvae reared on untreated or Empire treated diet, could alter the susceptibility of F1 fourth instar larvae of S. littoralis to some insecticides. Substerilizing doses (25, 50 and 100 Gy) of gamma radiation were used for pupal irradiation. The results revealed that: (1) pupal irradiation alone or preceded by chlorpyrifos/diflubenzuron (Empire) treatment had the same effect, both equally decreased the tolerance of F1 larvae to deltamethrin (Decis) and cyanophos (Cyanox), but treatment with Empire alone didn’t affect the response of these larvae; (2) no differences in the level of susceptibility of F1 larvae to methomyl/diflubenzuron (Deenate) or chlorpyrifos/Dowco 439 (Delfos) was observed whether Empire and irradiation with lower doses were applied in a combination or alone; (3) the susceptibility of F1 larvae to Empire wasn’t affected as a result of separate treatments with Empire or irradiation, while insecticide-irradiation combination greatly enhanced it’s effectiveness; and (4), the effect of irradiation alone was more pronounced in increasing the toxicity of chlorpyrifos (Dursban); cyfluthrin (Baythroid) and thiodicarb (Larvin), but when combined with Empire, different levels of tolerance to those insecticides were noticed. Thus, gamma irradiation when applied alone has increased the susceptibility of S. littoralis F1 larvae to all tested insecticides, except Empire. Furthermore, F1 larvae from two irradiated parents had some relative susceptibility to the tested insecticides, the degree was probably great enough to achieve more favorable integrated control by the application of any one of these insecticides in the field, being treated by the release of sterile moths of the cotton leaf worm, S. littoralis.